LIVING LABS IN BRAZILIAN AGRIBUSINESS: AN ANALYSIS OF THE POTENTIAL FOR OPEN INNOVATION AND CO-CREATION IN NEMATODE CONTROL BASED ON THE STOLLER, LMPP, AND USINA SÃO LUIZ CASE STUDY - Otoboni, Carlos; Luvizotto, Caroline Kraus; Fisher, Hannes; Sanchez, José Vitor; Mazega, Márcio Gabriel; de Almeida, Milena Carolina; Rolon, Ryan Espinoza (Seven Editora, 2025)
This article analyzes the application of the Living Labs model in the context of Brazilian agribusiness, highlighting its ability to promote open innovation, sustainability, and co-creation among public, private, and academic actors. The research uses as its empirical object the experiment developed through a partnership between Stoller, the Plant Monitoring and Protection Laboratory (LMPP), and Usina São Luiz, focused on nematode management. The study seeks to understand how the Living Lab methodology contributes to collaborative innovation processes from the perspective of field experimentation and the integration of scientific knowledge with productive practice. The analysis concludes that agricultural Living Labs represent a new paradigm of systemic and sustainable innovation in the sector by integrating technical-scientific knowledge with the practical expertise of rural producers.DOI: https://doi.org/10.56238/sevened2025.039-007